Immunomodulatory Effects of Probiotics Bacteria Lactobacillus acidophilus and Streptococcus thermophilusas Fermenter in Soygurt - Sayu Putu Yuni Paryati, Siska Telly Pratiwi, Evi Apriani Sitorus, Dianti Nursafitri Sundarti, Susanti Ratunanda, Indarti Trimurtini, Eka Noneng Nawangsih (International Journal of Advanced Science and Technology, 2020)
Probiotics commonly are produced from Lactic Acid Bacteria (LAB). Lactobacillus acidophilus and Streptococcus thermophilus are known to grow well in soy milk media. Probiotics conferred many benefits, one of them is as an immunomodulator. Many studies have shown that probiotics can stimulate the immune system, either non-specific or specific immune responses, such as stimulating increased activity of macrophage phagocytosis and antibody titer. This study aimed to examine the effects of immunomodulatory L. acidophillus and S. thermophillus as bacteria fermenter in soygurt. Twenty four of mice were divided in four groups: control negative, mice that treated the soygurt L. acidophillus, mice that treated the soygurt S. thermophillus, and mice that treated the combination soygurt. Mice were given the soygurt in 10 days and induced E. coli on days 9. The mice immune response was measured by observing the activity of phagocytosis and antibody titer. The study did not show activity of phagocytosis. The result of study showed that of monocyte numbers increased in peritoneum liquid. It indicated the enhancement of immune response in mice. There was significant difference between control group and treated group (p≤0,05) but no significant difference (p≥0,05) among the treated groups. There are significant differences in antibody titres by treating soygurt L. acidophilus (p = 0.030) and soygurt combination (p = 0.031) compared to the control group. The mice grouptreated S. thermophilus yield an increase in antibody titer but not significant (p≥0,05) compared with the control group. Keywords: Lactobacillus acidophilus, macrophage phagocytosis activity, soygurt, probiotic, Streptococcus thermophilus.